Necesidad de reformar el artículo 82 del código de la niñez y adolescencia para permitir el trabajo de los adolescentes de edad mínima 14 años, en el Ecuador - Garnica Castillo, Almida María (2017)
The conditions of adolescents reveal deep in the quality of life of a society, the values in a country and its concern for the future. The importance of the work of the adolescents of minimum age of 14 years, focuses on analysing whether the legislation concerning this issue has caused positive or negative effects. There are various forms of work performed by adolescents, work, is a physical activity, mental, social or morally productive for the teenager as many times do not interfere with their schooling, it is more according to the first national survey on child labor the 75.1 % of the children, working children and adolescents attending classes. To determine the extent to which it is beneficial to the work of the adolescents from the 14 years, without harm to their health, education, 20 surveys were applied to lawyers in free exercise, 10 adolescents than in the present work, in addition to the interview to 3 lawyers more than free exercise, the National Commissioner and the President of the Council of Children and Adolescents, with the information collected in the results were achieved. With the information from the literature review and the results obtained in the interview, survey could not comply with the hypothesis, because if you can incorporate in the Childhood and Adolescence Code the employment of adolescents 14 years of age; because in our Constitution of the Republic, is established all the rights and guarantees that we all Ecuadorian citizens. The methodology used was crucial for the development of this study, was based on a bibliographic and documentary field, with a qualitative and quantitative approach that allowed an analysis of the authorities investigated and exploratory and descriptive type for the exploration of the problem based on empirical data of the objective of this study. The methods used were the materialistic - historical, scientific, deductive, inductive - descriptive, analytical and statistical method, all together were the fundamental basis to support this legal study.